2017
DOI: 10.1159/000485011
|View full text |Cite
|
Sign up to set email alerts
|

Association of Functional Genetic Variants of HOTAIR with Hepatocellular Carcinoma (HCC) Susceptibility in a Chinese Population

Abstract: Background/Aims: The HOX transcript antisense intergenic RNA (HOTAIR), a long non-coding RNA (lncRNA), plays an important role in the pathogenesis and progression of multiple tumors. The aim of the present study was to evaluate whether common single nucleotide polymorphisms (SNPs) in HOTAIR are related to hepatocellular carcinoma (HCC) susceptibility in a Chinese population. Methods: We genotyped three SNPs of HOTAIR in a hepatocellular carcinoma (HCC) case-control study, including 482 cases and 520 control su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 28 publications
(34 reference statements)
0
14
0
Order By: Relevance
“…In a study evaluating whether common single nucleotide polymorphisms (SNPs) in HOTAIR are related to HCC susceptibility, significant association was observed between HOTAIR rs920778 C>T polymorphism and risk of HCC occurrence; in addition, the rs920778 TT genotype induced significantly higher expression levels of HOTAIR, compared with the CC genotype. These findings suggest that the HOTAIR SNP rs920778 could be used to predict HCC development, although further studies were required to confirm the findings [50].…”
Section: Hotair In Hepatocellular Carcinomamentioning
confidence: 77%
“…In a study evaluating whether common single nucleotide polymorphisms (SNPs) in HOTAIR are related to HCC susceptibility, significant association was observed between HOTAIR rs920778 C>T polymorphism and risk of HCC occurrence; in addition, the rs920778 TT genotype induced significantly higher expression levels of HOTAIR, compared with the CC genotype. These findings suggest that the HOTAIR SNP rs920778 could be used to predict HCC development, although further studies were required to confirm the findings [50].…”
Section: Hotair In Hepatocellular Carcinomamentioning
confidence: 77%
“…Xue et al found that SNP rs7958904 was associated with a significant protective effect for colorectal cancer. Additionally, Li et al reported that rs920778 presented an increased association with HCC risk. However, few studies exist on the effect of HOTAIR SNPs on HCC incidence and development.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, Li et al 23 reported that rs920778 presented an increased association with HCC risk. However, few studies exist on the effect of HOTAIR SNPs on HCC incidence and development.…”
mentioning
confidence: 99%
“…To date, SNPs of more than 20 lncRNAs have been identified in human malignant tumors . For example: HOTAIR, as one of the most closely investigated lncRNAs, polymorphisms of which have been studied in gastric cancer, prostate cancer, cervical cancer, breast cancer, hepatocellular carcinoma, oral cancer , and lung cancer . However, there are few reports on SNPs of lncRNAs in RCC.…”
Section: Discussionmentioning
confidence: 99%